Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3233/jad-180777
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DS2/KIR2DL2/HLA-C1 Haplotype Is Associated with Alzheimer’s Disease: Implication for the Role of Herpesvirus Infections

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder, where neuroinflammation and immune cells are key pathological factors. Recently it was suggested a possible association between AD and human herpesvirus 6 (HHV-6) infection. Since we recently observed that Multiple sclerosis patients with KIR2DL2 expression on Natural Killer (NK) cells are more susceptible to herpesvirus infection, we tested the possible implication of KIR/HLA genetic for HHV-6A infection. We identified, for the first time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
2
25
0
1
Order By: Relevance
“…As previously reported, HHV-6A and HHV-6B viruses can infect NK cells (Rizzo et al, 2019). Here we showed that NK92 cells are permissive to HHV-6A, HHV-6B, and HHV-7, with a high viral amount 3 days post infection (d.p.i.)…”
Section: Hhv-6a Hhv-6b and Hhv-7 Infect Nk Cellssupporting
confidence: 77%
“…As previously reported, HHV-6A and HHV-6B viruses can infect NK cells (Rizzo et al, 2019). Here we showed that NK92 cells are permissive to HHV-6A, HHV-6B, and HHV-7, with a high viral amount 3 days post infection (d.p.i.)…”
Section: Hhv-6a Hhv-6b and Hhv-7 Infect Nk Cellssupporting
confidence: 77%
“…HHV-6A DNA extraction and analysis was performed as previously described (Rizzo et al, 2019). Briefly, real-time quantitative polymerase chain reaction (qPCR) specific for the U94 gene was used to determine HHV-6A DNA presence and load.…”
Section: Hhv-6a Cell Infection and Assays For Hhv-6 Detectionmentioning
confidence: 99%
“…Genetic analysis of late‐onset AD has uncovered a number of single nucleotide polymorphisms (SNPs) that are associated with the risk for AD, including KIR2DS2/KIR2DL2/HLA‐C1, apolipoprotein E (APOE), phosphatidylinositol binding clathrin assembly protein (PICALM), complement receptor 1 (CR1) and clusterin (CLU), glycoprotein carcinoembryonic antigen‐related cell adhesion molecule‐16, B‐cell lymphoma‐3, translocase of outer mitochondrial membrane 40 homolog (TOMM‐40), apolipoprotein C‐I (APOC1), and C‐type lectin domain A family‐16 member, paired immunoglobulin‐like type 2 receptor (PILRα), nectin‐2 (also known as poliovirus receptor‐related 2, PVRL‐2) . Nectin‐2, TOMM‐40, APOE, and APOC1 are closely located in chromosome 19.…”
Section: Susceptible Genetic Factors Of Ad Facilitate Herpesviral Infmentioning
confidence: 99%